A cross-sectional and exploratory geospatial study of bovine viral diarrhea virus (BVDV) infections in Swines in the São Paulo State, Brazil - Almeida, Henrique Meiroz de Souza [UNESP]; Gatto, Igor Renan Honorato [UNESP]; dos Santos, Anne Caroline Ramos [UNESP]; Ferraudo, Antônio Sérgio [UNESP]; Samara, Samir Issa [UNESP]; de Oliveira, Luís Guilherme [UNESP] (Univ Agriculture, Fac Veterinary Science, 2017)
Reports of the first isolation of a ruminant Pestivirus (BVDV) from swine were in 1973, and since then the occurrence of cross-infections has been reported in many countries and the serological cross-reaction between the Classical Swine Fever Virus (CSFV) and the Bovine Viral Diarrhea Virus (BVDV) antibodies can interfere in Classical Swine Fever (CSF) eradication. This study focused on establishing the prevalence of antibodies anti-BVDV in pigs of non-technified rearing farms, associating risk factors to the infection and using geospatial analysis tools to identify high risk of positive herd's areas and other epidemiological features. A set of 360 serum samples from 56 herds were collected and analyzed using the virus neutralization test (VN). In total, 4.72% (17) of the samples had antibodies and 26.79% (15) of the herds had at least one positive animal. The titers obtained ranged from 640 to 10 for BVDV-1 and 80 to 10 in BVDV-2. The Kernel's distribution map showed two high risk of infection areas, which were associated using a statistical multiple correspondence analysis (MCA) with the presence of bovine herds and median total swine herd size. The use of raw milk in the swine feed was associated with disease presence. In conclusion, BVDV antibodies were detected in swine serum and possible links between bovines and swine herds in transmission of BVDV from cattle to swine and the problems that might arise from serological cross-reaction in CSF tests due to the presence of anti-BVDV antibodies in swine serum are discussed. (C) 2017 PVJ. All rights reserved
Keywords: Geospatial distribution; Infectious diseases; Ruminant Pestivirus; Virus neutralization